Impact of Coastal Community Empowerment Development Project-International Fund For Agriculture - Imran Tajuddin (STIE Amkop Makassar, 2022)
Objectively, this study was conducted to analyze the impact of the Coastal Community Development Project in collaboration with the International Fund for Agriculture Development (CCDP-IFAD) on education, business experience, involvement of women and men in the program, economic improvement of recipient communities, and program effectiveness. In improving the welfare of society. Literature studies and field studies carried out data collection techniques through interviews, observations, and documentation. Using a stratified random sampling method, samples were taken with 88 respondents consisting of 34 processors, eight farmers, 23 marketers, and 23 fishers. The results showed that the coastal communities who were assisted by the CCDP-IFAD program had a sufficient level of education and experience so that they were able to receive the program well. In addition, the level of women's involvement in the project of 50% has met the project requirements that require the involvement of women at 20%. The results also show that the CCDP-IFAD program is effective for the processing group with a value of 2.5 or 63.12%, the cultivation group 2.1 or 54.86%, and less effective for the marketer group of 1.98 or 45.75%, and the fishing group with a value of 1 .93 or 40.36%.